Motivational perspective on students cheating during COVID-19 pandemic as the basic variable to create research instrument - Dewi Kurniawati; Iga Yusdisti; Alifah Fadiyah; Haniifah Fawziyyah; Liza Nadia Lianza (Journal of Applied Studies in Language, 2021)
COVID-19 pandemic brought all activities remotely, especially in education. All institutions tried to provide an E-Learning platform to facilitate the teaching-learning process for delivering the material, teaching process and conducting an assessment. All were changing, focusing on the assessment process; not all institutions could provide online proctoring technology, which opened cheating among students. This study was conducted using a structural literature review to find the dependent and independent variables in designing a questionnaire. The data was taken by typing keyword academic dishonesty in google scholar during January – March 2021 and took three journals at random to identify the theory of motivation and honesty among students in cheating. The instrument was evaluated by quantitative research to assess the validity and reliability coefficient value. This study provided us with the fact that collaboration, lack of mutual trust and policy, as part of academic dishonesty types, were the main factors challenging the students to act dishonesty in doing online tests. The instrument tested was also valid with all points are on the range of 0.6-0.8, and for the reliability, showed the best result on point 0.94. The validity and reliability measurement shows that the instrument is acceptable for measuring the students’ motivation in doing academic dishonesty and can be conducted for a larger population with more varied backgrounds and levels.